The Impact of Eight Weeks of Aquatic Plyometric Training on the Explosive and Agility Capabilities of Swimmers - Salama, Rafaa Abou; Baaziz, Mohamed; Khalfoun, Jihen; Omar, Mohaned; Chanti, Ali; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
The objective of this study is to examine the impact of eight weeks of aquatic plyometric training on the explosive and agility abilities of swimmers. The following keywords were used: The objective of this study was to ascertain the impact of aquatic plyometric training (APT) on explosive power and agility. A training program incorporating APT was implemented on a sample of 20 swimmers. The findings revealed that utilizing APT at a depth up to the pelvis for 8 weeks and 3 times a week led to statistically significant differences and improvements in explosive power and agility. The effect size values for the two variables were 0.97 and 0.97, respectively. The researcher recommended the use of APT as a viable alternative to plyometric exercises on hard ground for enhancing explosive power and agility, while also reducing the risk of muscle and tendon injuries.